Small extracellular vesicles modulated by αVβ3 integrin induce neuroendocrine differentiation in recipient cancer cells. Issue 1 (1st January 2020) - Quaglia, Fabio; Krishn, Shiv Ram; Daaboul, George G.; Sarker, Srawasti; Pippa, Raffaella; Domingo-Domenech, Josep; Kumar, Gaurav; Fortina, Paolo; McCue, Peter; Kelly, William K.; Beltran, Himisha; Liu, Qin; et al.
ABSTRACT: The ability of small extracellular vesicles (sEVs) to reprogram cancer cells is well established. However, the specific sEV components able to mediate aberrant effects in cancer cells have not been characterized. Integrins are major players in mediating sEV functions. We have previously reported that the αVβ3 integrin is detected in sEVs of prostate cancer (PrCa) cells and transferred into recipient cells. Here, we investigate whether sEVs from αVβ3-expressing cells affect tumour growth differently than sEVs from control cells that do not express αVβ3. We compared the ability of sEVs to stimulate tumour growth, using sEVs isolated from PrCa C4-2B cells by iodixanol density gradient and characterized with immunoblotting, nanoparticle tracking analysis, immunocapturing and single vesicle analysis. We incubated PrCa cells with sEVs and injected them subcutaneously into nude mice to measure in vivo tumour growth or analysed in vitro their anchorage-independent growth. Our results demonstrate that a single treatment with sEVs shed from C4-2B cells that express αVβ3, but not from control cells, stimulates tumour growth and induces differentiation of PrCa cells towards a neuroendocrine phenotype, as quantified by increased levels of neuroendocrine markers. In conclusion, the expression of αVβ3 integrin generates sEVs capable of reprogramming cells towards an aggressive phenotype.